Viral hepatitis in the state of Piauí: epidemiological characterization in a hematology and hemotherapy center - Oliveira, Evaldo Hipólito (2020)
Viral hepatitis are infectious diseases that are characterized by presenting inflammatory reactions in the liver, which may be of acute or chronic evolution. They are caused by hepatotropic viruses, designated by letters of the alphabet and, due to their high prevalence and potential complications, constitute a major public health problem. This research aimed to analyze the prevalence of hepatitis “b” and “c” in blood donors from the state of Piauí, through an epidemiological study of patients who applied for blood donation at the Piauí Hemocenter (HEMOPI) January 2008 to December 2010. We obtained the following results. In 2008 0.33% of donors were infected with HBV and 0.41% with HCV, in 2009 0.24% were infected with HBV and 0.19% with HCV. , and in 2010 0.14% for HBV and 0.16% for HCV. This research conducted with data obtained from the Piauí Hemocenter demonstrates a low prevalence of Hepatitis B and C of donor candidates, compared to several studies conducted in Hemonuclei from other Brazilian states.